On the broken rotor bar diagnosis using time-frequency analysis: 'Is one spectral representation enough for the characterisation of monitored signals?' - Panagiotou, Panagiotis A.; Arvanitakis, Ioannis; Lophitis, Neophytos; Antonino-Daviu, Jose A.; Gyftakis, Konstantinos N. (My University, 2019)
This work enhances the knowledge of the diagnostic potential of the broken bar fault in induction motors. Since a series of studies have been published over the years regarding condition monitoring and fault diagnostics of these machines, it is essential to reach a common ground on why - sometimes - different techniques render different results. In this context, an investigation is provided with regards to the optimal window that should be adopted for the implementation of a proper time-frequency analysis of the monitored signals. On this agenda, this study attempts to set lower and upper bound limits for proper windowing from the digital signal processing point of view. This is done by proposing a formula for the lower limit, which is derived according to the specific frequencies one desires to put under inspection and which are the fault-related signatures. Finally, a discussion on the upper bound is put onwards; results from finite-element simulations are examined with the discussed approach in both the transient regime and the steady state, while experimental results verify the simulations with satisfying accuracy.
Keywords: Condition monitoring; Induction motors; broken rotor bar